Pelatihan Integrasi Perplexity Untuk Penelusuran Literatur Dan Penulisan Karya Ilmiah Di SMAN 5 Makassar - Andi Shridivia Nuran; Aulia Rahmah; Hamidah Hamris; Azizah Fauziah Misbahuddin; Andi Nur Faisal (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2025)
The rapid development of information and communication technology has created challenges for students in accessing credible scientific references and writing structured academic papers. At SMAN 5 Makassar, many students, especially those in the Kelompok Ilmiah Remaja (KIR), reported difficulties in conducting literature searches, evaluating reliable sources, and managing scientific references effectively. To address this issue, a community service program was conducted through training on the integration of Perplexity AI as a tool for literature search and scientific writing. The training was held on May 5, 2025, involving 30 students and supervising teachers. The implementation methods included interactive lectures, demonstrations, guided practice, group discussions, and reflection sessions. Evaluation was carried out through direct observation and performance assessments during the practice sessions. The results showed a significant improvement in students’ digital literacy and research skills. Before the training, less than 20% of participants were able to independently search and manage scientific references; after the program, more than 80% successfully utilized Perplexity AI to find academic references, structure scientific papers, and apply academic ethics, including plagiarism avoidance. Positive feedback was also received from teachers, and a sustainable mentoring group was formed to maintain the program’s impact. This initiative demonstrates that integrating AI-based tools can effectively enhance students’ research competence and foster a more adaptive digital learning ecosystem in schools